Reply to: "Multiparametric magnetic resonance imaging to predict clinical outcomes in patients with chronic liver disease: a cautionary note on a promising technique". - Pavlides, M; Banerjee, R; Kelly, C; Robson, M; Neubauer, S; Barnes, E (Elsevier, 2016)
We read with interest the letter by Chouhan et al., which raises several points for discussion in relation to our manuscript on “Multiparametric magnetic resonance imaging to predict clinical outcomes in patients with chronic liver disease” [1]. We agree that our study size is relatively small (in comparison to studies examining transient elastography or serum based biomarkers), and as such we are clear that we see this as a proof of principle study. Nevertheless, our study is the largest to date to report on the prognostic value of a magnetic resonance (MR) T1 mapping technique in the liver, and the relatively high adverse event rate of approximately 10% in this patient population (compared to the 4% in the transient elastography study in Calgary [2] and the 13% seen with ELF in a population that excluded extrahepatic disease [3]) allowed us to draw statistically significant conclusions regarding the ability of the MR to predict negative clinical outcomes in liver disease.